Gold-catalyzed tandem reactions of amide–aldehyde–alkyne coupling and cyclization-synthesis of 2, 4, 5-trisubstituted oxazoles. Issue 12 (9th October 2015) - Querard, Pierre; Girard, Simon A.; Uhlig, Nick; Li, Chao-Jun
Abstract : We report the first cationic gold(i )-catalyzed one-pot reaction of amide, aldehyde and alkyne followed by cyclization, to successfully access highly substituted oxazoles derivatives in good yields. Abstract : We report the first cationic gold(i )-catalyzed one-pot reaction of amide, alkyne and aldehyde followed by cyclization, to successfully access highly substituted oxazoles derivatives in good yields. A single catalyst allows the occurring of this multi-step reaction atom- and step-economically, with water as the only theoretical side product.